The Effect Of Using Leaflet Media To Reduce Anxiety In Pregnant Women In Trimester III During The Covid-19 Pandemic In The Andalas Health Center - Uliy Iffah; Hindun Mila Hudzaifah; Ranny Shabrina; Lulisa Desrama Tasya (Journal of Midwifery, 2021)
Anxiety in pregnant women can arise, especially in the third trimester of pregnancy until delivery, where during this period pregnant women feel anxious about various things such as anxiety about the baby's birth process and the pain they feel. Covid-19 causes pregnant women to be very anxious about their pregnancy and also with the rules for preparing for childbirth. The purpose of this study was to determine the effect of using leaflet media on the level of anxiety in third-trimester pregnant women during the Covid-19 pandemic at the Andalas Health Center, Padang City.  The type of research used is quasi-experimental with a control group pretest-posttest design. In this research design, the experimental group received education using leaflet media, while the control group was given conventional-based education (without using media). The results of The p-value is 0.000, so it can be concluded that there is a difference in anxiety before and after being given health education. The provision of health education interventions about childbirth can reduce anxiety scores in third-trimester pregnant women.